Penerimaan diri orang tua dengan anak tunagrahita: Adakah peranan dukungan sosial? - Nur Amalina Zuhruf Karin; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between social support and self-acceptance of parents who have mentally retarded children. The population in this study were the parents of students at SLB Al-Azhar Waru. Respondents in this study were taken using a purposive sampling technique with a total of 60 respondents. This research instrument uses a scale of social support and a scale of self-acceptance. Based on the results of data analysis using the product moment correlation, the results obtained were rxy = 0.579 and p = 0.000, which is significant, meaning that there is a positive relationship between social support and self-acceptance of parents who have mentally retarded children at SLB Al-Azhar Waru. The effective contribution in this study was 0.335, which means that social support has an effect of 33.5% on self-acceptance of parents, the rest is influenced by other factors. Keywords: accepting yourself; mentally retarded; social support. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan social dengan penerimaan diri orang tua yang memiliki anak tunagrahita. Populasi dalam penelitian ini merupakan orang tua dari siswa di SLB Al-Azhar Waru. Responden dalam penelitian ini diambil dengan menggunakan teknik purposive sampling dengan jumlah sebanyak 60 responden. Instrumen penelitian ini menggunakan skala dukungan social dan skala penerimaan diri. Berdasarkan hasil analisis data dengan menggunakan korelasi product moment diperoleh hasil rxy = 0,579 dan p = 0,000 yang berarti signigfikan, artinya terdapat hubungan positif antara dukungan social dengan penerimaan diri orang tua yang memiliki anak tunagrahita di SLB Al-Azhar Waru. Sumbangan efektif dalam penelitian ini sebesar 0,335 yang artinya dukungan social memiliki pengaruh sebesar 33,5% terhadap penerimaan diri orang tua selebihnya dipengaruhi oleh faktor lain. Kata kunci: Dukungan Sosial; Penerimaan Diri; Tunagrahita.